AREAdata: a worldwide climate dataset averaged across spatial units at different scales through time - Smith,TP; Stemkovski,M; Koontz,A; Pearse,WD (2021)
ABSTRACT In an era of increasingly cross-discipline collaborative science, it is imperative to produce data resources which can be quickly and easily utilised by non-specialists. In particular, climate data often require heavy processing before they can be used for analyses. Here we describe AREAdata, a free-to-use online global climate dataset, pre-processed to provide the averages of various climate variables across differing administrative units ( e . g ., countries, states). These are daily estimates, based on the Copernicus Climate Data Store’s ERA-5 data, regularly updated to the near-present and provided as direct downloads from our website ( https://pearselab.github.io/areadata/ ). The daily climate estimates from AREAdata are consistent with other openly available data, but at much finer-grained spatial and temporal scales than available elsewhere. AREAdata complements the existing suite of climate resources by providing these data in a form more readily usable by researchers unfamiliar with GIS data-processing methods, and we anticipate these resources being of particular use to environmental and epidemiological researchers.